Managerial accounting and finance for hospitality operations - Cabrera, Ma. Elenita Balatbat (Manila, 2007)
The book presents managerial accounting and finance concepts and how they apply to specific operations within the hospitality industry.
Keywords: Hospitality industry- Accounting; Hotel management